2021
DOI: 10.3390/ma14041009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Boundary Conditions on Numerical Homogenization of High Performance Concrete

Abstract: Concrete is the most widely used construction material nowadays. We are concerned with the computational modelling and laboratory testing of high-performance concrete (HPC). The idea of HPC is to enhance the functionality and sustainability of normal concrete, especially by its greater ductility as well as higher compressive, tensile, and flexural strengths. In this paper, the influence of three types (linear displacement, uniform traction, and periodic) of boundary conditions used in numerical homogenization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…All tests assumed linear elasticity, but the method can be applied to nonlinear material laws without any changes. 10 Of course, the efficient implementation of the double fine material grid (12) would not be possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All tests assumed linear elasticity, but the method can be applied to nonlinear material laws without any changes. 10 Of course, the efficient implementation of the double fine material grid (12) would not be possible.…”
Section: Discussionmentioning
confidence: 99%
“…In Pahr and Böhm, 10 the authors demonstrate that these boundary conditions yield valid results also for nonlinear material laws. Panyasantisuk et al 11 and Denisiewicz et al 12 confirmed that also in the nonlinear regime, KUBC provide an upper bound to the apparent stiffness and yield behavior, while SUBC lead to a lower estimate of the effective values. PMUBC provide more compliant linear and nonlinear values.…”
Section: Boundary Conditionsmentioning
confidence: 95%
See 1 more Smart Citation
“…where ε(u) is the micro strain and x is the position vector on the boundary ∂Ω. This method presents the advantage of having no restriction to its application except that no rigid part must intersect the boundary [32]. Uniform traction boundary conditions consist of applying on the boundary of the RVE the stress vector field that would occur if the stress were uniform inside the RVE…”
Section: Linear Displacement and Uniform Traction Boundary Conditionmentioning
confidence: 99%
“…In a micromechanical analysis of the RVE, applying periodic boundary conditions (PBC) is more advantageous over homogeneous boundary conditions [34,35]. In order to apply PBC, RVE must be continuous across its boundary when it is repeated in the space.…”
Section: Periodic Copies Additionmentioning
confidence: 99%